1996
DOI: 10.1007/bf00182060
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of nm23 H1/nucleoside diphosphate kinase A mRNA associated with adenocarcinoma of the prostate

Abstract: Overexpression of the nm23H1 gene has been associated with the suppression of metastasis in several solid tumors. However, in colorectal carcinoma and neuroblastoma, increased levels of nm23 H1 nucleoside diphosphate kinase A (NDPKA) mRNA are associated with tumorigenesis. To determine the role of rim23 H1/ NDPKA in the prostate, normal and/or malignant tissue samples from 29 consecutive patients were studied. Levels of rim23 H1/NDPKA mRNA and nm23 H1/NDPKA mRNA protein were determined in tissue from 18 and 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…266,267 Another study found that, unlike breast cancer and melanoma in which decreased NM23 is associated with metastases, overexpression of the NM23 gene occurs frequently in adenocarcinoma of the prostate and may even be an early event of PC tumorigenesis. 268 Levels of NM23 mRNA and protein were both increased in metastatic PC lymph nodes compared to normal prostate tissue. Furthermore, cancer specimens and adjacent PIN showed immunoreactivity with NM23 antibody, but there was weak or no reactivity in normal prostatic tissue.…”
Section: Cd44 Metastasis Suppressor Genementioning
confidence: 91%
See 1 more Smart Citation
“…266,267 Another study found that, unlike breast cancer and melanoma in which decreased NM23 is associated with metastases, overexpression of the NM23 gene occurs frequently in adenocarcinoma of the prostate and may even be an early event of PC tumorigenesis. 268 Levels of NM23 mRNA and protein were both increased in metastatic PC lymph nodes compared to normal prostate tissue. Furthermore, cancer specimens and adjacent PIN showed immunoreactivity with NM23 antibody, but there was weak or no reactivity in normal prostatic tissue.…”
Section: Cd44 Metastasis Suppressor Genementioning
confidence: 91%
“…Furthermore, cancer specimens and adjacent PIN showed immunoreactivity with NM23 antibody, but there was weak or no reactivity in normal prostatic tissue. 267,268 More work is thus needed to clarify the role and clinical implications of NM23 in PC.…”
Section: Cd44 Metastasis Suppressor Genementioning
confidence: 99%
“…44 In clinically signi®cant CaP it has been found that nm23-H1 mRNA levels were more than 10-fold higher than levels found in latent CaP or normal prostates, which increased with tumour grade. 45,46 Strong nm23-H1 immunostaining is also frequently found in malignant cells of localized CaPs and metastatic sites of CaP. 47,48 Although encouraging, further studies of the contribution of nm23 regulation in loss of metastasis suppression in CaP are needed.…”
Section: Potential Future Prognostic Markers In Prostate Cancermentioning
confidence: 99%
“…Low levels of the nm23-H1 gene expression increase metastatic potentials in a variety of tumour types and transfected cells (Betke et al, 1998;de la Rosa et al, 1995;Guo et al, 1998;Hartsough and Steeg, 1998;Russell et al, 1998;Tagashira et al, 1998;Yoshida et al, 1998;. However, numerous tumours and highly proliferative cells overexpress the nm23-H1 gene (Chang et al, 1994;Gazzeri et al, 1996;Jensen et al, 1996;Keim et al, 1992;Leone et al, 1993;Muller et al, 1998;Sastre-Garau et al, 1992a;Shimada et al, 1998). These results suggest an overexpression of nm23-H1 linked to early stages of cancer and a loss of expression in more advanced stages.…”
Section: Introductionmentioning
confidence: 99%